The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0959683617702236
|View full text |Cite
|
Sign up to set email alerts
|

Paleoparasitological investigations on the Neolithic lakeside settlement of La Draga (Lake Banyoles, Spain)

Abstract: Paleoparasitological analyses were conducted on samples from the Neolithic lakeside settlement of La Draga in Spain (5320-4980 BC). Conventional microscopic analysis revealed the presence of tapeworms (genus Taenia/Echinoccocus and Diphyllobothrium), roundworms (genus Trichuris, Capillaria, and Ascaris), rumen fluke (genus Paramphistomum), and Acanthocephalan (genus Macracanthorhynchus). In addition, genetic analysis demonstrated the presence of the lancet liver fluke (Dicrocoelium dendriticum) and the human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…In Spain, a Neolithic site La Draga, dated of 7270–6930 BP, showed the presence of two capillariid morphotypes with different ornamentations. Considering the characteristics of the eggs, especially the ornamentation, the authors suggested that the reticulated-type egg was from a Bovidae infection and the punctuated-type was probably related with fish-eating habits or the presence of rodents [34].…”
Section: Resultsmentioning
confidence: 99%
“…In Spain, a Neolithic site La Draga, dated of 7270–6930 BP, showed the presence of two capillariid morphotypes with different ornamentations. Considering the characteristics of the eggs, especially the ornamentation, the authors suggested that the reticulated-type egg was from a Bovidae infection and the punctuated-type was probably related with fish-eating habits or the presence of rodents [34].…”
Section: Resultsmentioning
confidence: 99%
“…In a Spanish Neolithic site, Macracanthorhynchus sp. was found and associated with the consumption of pork evidenced by the finding of pig bones (Maicher et al 2017). Other sporadic findings of unidentified Acanthocephala species were made in the Old World (Bouchet et al 1989(Bouchet et al , 2000.…”
Section: Discussionmentioning
confidence: 93%
“…where such finds are not rare. It has an important impact for the development of new research directions there, and on the other hand, it contributes to the database which is already available from comparable prehistoric waterlogged contexts in Europe (Bouchet et al, 2003;Le Bailly et al, 2003;Kühn et al, 2013;Maicher et al, 2017 and Link-http://www.scirpus.ca/dung/mammal.php). While this type of find material is scarce and hard to obtain, and therefore only rarely investigated, each analysis of it counts and is original and exceptional.…”
Section: Discussionmentioning
confidence: 99%